Psychosocial and Cardiac Outcomes of Yoga for ICD Patients: A Randomized Clinical Control Trial - STEFANIE C. F. TOISE; Samuel F. Sears; Mark H. Schoenfeld; Mark L. Blitzer; Mark Marieb; John H. Drury; Martin D. Slade; Thomas J. Donohue (2013)
Background Because as many as 46% of implantable cardioverter defibrillator (ICD) patients experience clinical symptoms of shock anxiety, this randomized controlled study evaluated the efficacy of adapted yoga (vs usual care) in reducing clinical psychosocial risks shown to impact morbidity and mortality in ICD recipients. Methods Forty‐six participants were randomized to a control group or an 8‐week adapted yoga group that followed a standardized protocol with weekly classes and home practice. Medical and psychosocial data were collected at baseline and follow‐up, then compared and analyzed. Results Total shock anxiety decreased for the yoga group and increased for the control group, t(4.43, 36), P < 0.0001, with significant differences between these changes. Similarly, consequential anxiety decreased for the yoga group but increased for the control group t(2.86,36) P = 0.007. Compared to the control, the yoga group had greater overall self‐compassion, t(–2.84,37), P = 0.007, and greater mindfulness, t(–2.10,37) P = 0.04, at the end of the study. Exploratory analyses utilizing a linear model (R 2 = 0.98) of observed device‐treated ventricular (DTV) events revealed that the expected number of DTV events in the yoga group was significantly lower than in the control group (P < 0.0001). Compared to the control, the yoga group had a 32% lower risk of experiencing device‐related firings at end of follow‐up. Conclusions Our study demonstrated psychosocial benefits from a program of adapted yoga (vs usual care) for ICD recipients. These data support continued research to better understand the role of complementary medicine to address ICD‐specific stress in cardiac outcomes.